Gender Inequality and Construction of Identity in ELT Scenario - Naz, Samia; Imtiaz Asif, Saiqa (The Journal of Humanities & Social Sciences, 2022)
The paper focuses on male and female learners‟ notion of symbolic capital for construction of identity in Pakistani society where gender inequality leads to low investment on daughters‟ education. This research answers following questions: 1. Does gender discrimination exist in different social classes? 2. How does low investment on daughters‟ physical capital affect male and female English language learners‟ struggle for construction of identity? We used triangulation method to collect the data. One government and one private college (male and female each) were selected in two districts of Punjab. Thirty-two male and female low and high scorers studying at intermediate level and their parents were interviewed. We observed their homes. The results of college exams of class were analysed through SPSS1. The findings suggest that in spite of low investment on daughters‟ physical capital, the female students showed their commitment to build their identity.